Implementation and validation of 1D-3D CFD co-simulation for complete cooling system - Konstantinidis, Konstantinos (My University, 2020)
This thesis deals with the development and verification of a method that introduces coupling between one- and three- dimensional (1D and 3D) numerical simulations of a complete cooling system of a passenger car, as well as with the advantages of using such a platform. Such method is different from the common practise in the car industry, in which simplified models are typically used and they consider each component of the system as 1D. These models are typically based on emperical correlations. However, the 3D models solve for the differential equations that govern the fluid dynamics of a single-phase coolant and offer more detail in the analysis of a system. They are used for a part of the cooling system that the 1D models fail to capture the behaviour of the fluid and the physics. The rest of the cooling circuit will stay 1D, creating a need to device a method to couple 1D and 3D Computational Fluid Dynamics (CFD) software. The project was performed in the Cooling system development group at Volvo Cars. First, an analysis of the details of the cooling system and its modelling theory with 1D CFD models are introduced. Moreover, turbulence and its treatment in 3D CFD are described, while the theory behind coupling two CFD software is thoroughly established. The method for coupling has been developed with GT-SUITE for the 1D and STAR-CCM+ for the 3D. The inputs to the system, for example wall boundaries or operating points, are constant in time. A fully functional co-simulation platform is tested with different configurations. In each of them, a different component of the cooling system is simulated in 3D while the rest circuit runs in 1D. The results show stability in the co-simulation of all the configurations at and near the point that the coupling of the softwares occurs. At next, a discussion is made about the possible limitations of 1D modeling for these cases, with the conclusion of the advantages that were observed from the co-simulation in contrast to the extra computational cost it emerged. Lastly, there is an introduction of cases where cavity or boiling occurs in the cooling system, that require multiphase flow simulations, but the limitations in coupling the softwares didn’t allow further simulations. An investigation could be further performed in the future, following the assumption that the software will upgrade their co-simulation capabilities.
Keywords: Co-simulation; cooling system; coupling; GT-SUITE; 1D CFD; STAR-CCM+; 3D CFD